The Mediating Role of Automatic Thoughts in Relationship Between Attachment Style with Sexual Dysfunction and Marital Commitment: A Path Analysis - Nayereh Abdollahi; Shadi Jazini; Khaled Aslani; Abas Amanelahi (Gonabad University of Medical Sciences, 2020)
Background: This article explores the effects of attachment style and automatic thoughts on sexual dysfunction and marital commitment, using the path analysis model. This descriptive-correlational study was conducted on 375 married female students in Shahid Chamran University of Ahvaz, Iran, from 2016 to 2017. Methods: According to Morgan and Jersey table and the statistical population (375 people), the number of samples was calculated as 180. Female sexual function index, marital commitment questionnaire, behavioral systems questionnaire, and sexual modes inventory were used for data collection. Then, the obtained data were analyzed with the path analysis. Results: The results indicated that: 1. secure and insecure attachment styles had no direct effects on the sexual dysfunction, although they were significantly related to the automatic thoughts; 2. secure and insecure attachment styles had a direct impact on the marital commitment; 3. automatic thoughts were a mediating variable; 4. automatic thoughts were positively related to the sexual dysfunction and negatively related to the marital commitment. Based on the findings of this research, the relationship between attachment styles and automatic thoughts were predictors of sexual dysfunction and marital commitment.  Conclusion: Sexual function and commitment to marital relationships among couples can be increased by correcting automatic thoughts and providing necessary training about the attachment styles for parents.